PEMBELAJARAN KELAS RENDAH YANG DISESUAIKAN DENGAN PERKEMBANGAN PESERTA DIDIK SDN SERANG 17 - Valentri, Avi; Yusup, Maulana; Ningtias, Diniya; Hafidoh, Hafidoh; Rizqia, Mila Sofia; Suhernah, Suhernah (Universitas Tanjungpura, 2024)
The study used phenomenological research methods. Learner outcomes in grade 3 are prioritized from the beginning to the end of the semester, namely reading. Class management to be conducive to opening learning by praying, sitting neatly and continuing core activities in the learning process. Obstacles to students not being able to read. Teachers do not approve of the implementation of the independent curriculum because its implementation will have an impact on students. Conclusion The need to read is learning that is appropriate for the development of students in the lower grades and is prioritized. Habituation of the process of forming attitudes, behaviors that are relatively fixed, automatic through a repeated learning process. Class management remains conducive, opening learning with prayer, students are asked to sit neatly, entering core activities. Class management in improving learning provides appreciation and perception. Learner obstacles are done by doing morning activities by getting used to reading, providing independently books or reading materials, this activity is positive and runs smoothly. Conducting the school planning stage provides a variety of books, reading materials that interest students and carry out activities that increase students' interest in reading. Teachers disagree about the independent curriculum because of the impact on students, and are worried about the views of parents / guardians of students on their children's learning outcomes at school. In the independent curriculum, learning outcomes prioritize the strength of character as a developed value, the character that is the focus such as having the character of a Pancasila student.